Thornwaldt cyst - a disease or anomaly - Sotvoldiev Sohibbek Rakhmatullo o'gli; Ashurov Azimjon Mirzazhonovich (International Journal on Orange Technologies, 2020)
Thornwaldt's cyst is a rare congenital pathology characterized by the formation of a pathological cavity (pocket) in the nasopharynx. Discharge accumulates inside such a "pocket", which in the future becomes inflamed and a focus of purulent discharge is formed. Symptoms of the disease appear irregularly, but only as the discharge accumulates. Diagnosis of a cyst requires instrumental and radiation studies. Treatment - endoscopic removal of Thornwaldt's cyst or excision of the cyst using a surgical laser.